KEDUDUKAN HUKUM PEMEGANG HAK ATAS TANAH EIGENDOM VERPONDING DALAM PENGUASAAN TANAH OLEH PEMERINTAH - Sari, Ika Sistia Wulan; Setyadji, Sri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The purpose of writing this journal to examine the position and legal protection for holders of western land rights, namely Eigendom Verponding, which has not been converted into Property Rights in accordance with Law Number of 1960 concerning Basic Agrarian Provisions (’UUPA’), even time limit which is 20 years from the enactment of the LoGA until September 20, 1980, and there is a provision that states that the west does not change its land during the conversion period, it will be direct controlled by the but in fact, there are legal subjects who hold Eigendome Verpondinge land rights who have not converted their land directly controlled by the government and submitted an application to the court and the decision was to win the lawsuit of the Eigendom Verponding land right holder so the writer is interested to examine these problems, using normative juridical research methods through approach to laws, conceptual, cases and also history related to legal issues so that the research results are found that, in PP Number 24 of 1979 concerning Land Registration Article 24 paragraph (1))for the purposes of land registration of former rights can stillobe started systematically and sporadically. This has resulted in the absence of legal balance between the hierarchy of laws and regulations according to Article 7 of Law Number 12 of 2011 which has a higher degree of UUPA compared to Government Regulation Number 24 of 1997 so that regulations with a higher degree must refer to regulations of a higher degree, if in the legal principle lex superior derogat legi inferiori